2014
DOI: 10.1002/ange.201310317
|View full text |Cite
|
Sign up to set email alerts
|

Boron Clusters as Highly Stable Magnesium‐Battery Electrolytes

Abstract: Boron clusters are proposed as a new concept for the design of magnesium-battery electrolytes that are magnesiumbattery-compatible, highly stable, and noncorrosive. A novel carborane-based electrolyte incorporating an unprecedented magnesium-centered complex anion is reported and shown to perform well as a magnesium-battery electrolyte. This finding opens a new approach towards the design of electrolytes whose likelihood of meeting the challenging design targets for magnesium-battery electrolytes is very high.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 30 publications
2
59
1
Order By: Relevance
“…[41][42][43] These studies showed that modified structures would lead to high magnesium plating efficiencies with higher potential windows. After the first introduction of ar eversible magnesium battery,m any studies concerning magnesium organoaluminates and organoborates have been reported.…”
Section: Magnesiummentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43] These studies showed that modified structures would lead to high magnesium plating efficiencies with higher potential windows. After the first introduction of ar eversible magnesium battery,m any studies concerning magnesium organoaluminates and organoborates have been reported.…”
Section: Magnesiummentioning
confidence: 99%
“…After the first introduction of ar eversible magnesium battery,m any studies concerning magnesium organoaluminates and organoborates have been reported. [41][42][43] These studies showed that modified structures would lead to high magnesium plating efficiencies with higher potential windows. However,f or battery development, it is necessary to find as impler salt/electrolyte combination with high performance because the organosalts of magnesium are too expensive for real applications.T he first inorganic salt tested for am agnesium battery electrolyte was Mg(BH 4 ) 2 .…”
Section: Magnesiummentioning
confidence: 99%
“…In particular electrolytes based on magnesium borohydride, Mg(BH 4 ) 2 , have received significant attention since 2012, when Mohtadi et al . demonstrated the first fully inorganic and halide-free Mg electrolytes enabling reversible Mg plating and stripping78. In an effort to improve the safety, attempts have been made to replace the flammable organic solvents by ionic liquids91011.…”
mentioning
confidence: 99%
“…z E-mail: kthorn@umich.edu their practical application in batteries. 14 To avoid this problem, inorganic salts such as Mg(TFSI) 2 and Mg(BH 4 ) 2 in solutions based on traditional solvents 10,[15][16][17][19][20][21] or ionic liquids [22][23][24]26 have also been explored.Despite the recent growth in efforts to develop efficient magnesium electrolytes, many challenges remain. For example, formation of ionblocking passivation films on magnesium surfaces and compatibility with cathode materials (allowing reversible intercalation of Mg 2+ ) both remain challenges.…”
mentioning
confidence: 99%
“…2,7,8,11,12,27 Due to their halide content, Grignards, organohaloaluminates, and MACC are corrosive to non-noble metal substrates, which presents a challenge to their practical application in batteries. 14 To avoid this problem, inorganic salts such as Mg(TFSI) 2 and Mg(BH 4 ) 2 in solutions based on traditional solvents 10,[15][16][17][19][20][21] or ionic liquids [22][23][24]26 have also been explored.…”
mentioning
confidence: 99%